(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
Water is one of the most important resources on earth and a basic life need; all human activities towards social-economic developments depend on the availability of water. Groundwater accounts for about 0.06% of Earth’s available water and represents about 98% of the fresh water readily available to humans. Harnessing this important resource for productive uses such as irrigation, domestic and industrial water supplies would help to reduce poverty and vulnerability to water borne disease particularly in rural settlements. Groundwater development, exploitation, and supply chain in Nigeria is relatively low and needs a major transformation. Groundwater resource is required to meet the need of the rapid growth in population, urbanization, industrialization and competition for economic development. Although the management of groundwater in Nigeria is lagging behind the pace of development, and often, very little control is exercised in its exploitation, groundwater has gainfully impact on the rate and level of poverty and has transformed rural economies in most parts of the country, thereby alleviating poverty, reduce the rate of water related diseases and enhance economic growth. This paper emphasizes the impacts of groundwater developments on poverty reduction in Nigeria. The opportunities and economic sustainability presented by groundwater resource development are presented. Integrated approaches/strategies for sustainable management of groundwater resources with relevant recommendations for groundwater resource management are advocated.